Papan Belajar (Panjar) IPA Pada Pembelajaran Berdiferensiasi untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik Kelas VII - Satwika Trianti Ngandoh Ngandoh (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
This study aims to determine the effectiveness of the use of science learning board media in differentiated learning by improving students’ problem-solving abilities. The media used in this study is science learning board media that assists students in improving problem-solving skills. This study used a quasi-experimental research design of type 1 group pretest-posttest (initial test and final test in a single group). The subjects in this study were 36 students of grade VII SMP Negeri 14 Makassar. Data collection techniques include observation, tests, and documentation. Data analysis techniques using quantitative and qualitative descriptive analysis The data collection instrument consists of teacher activity observation sheets, student activity observation sheets, and problem-solving ability tests in the form of 10 numbers of description questions related to environmental pollution material. The results obtained are the average level of problem-solving ability of students in the sufficient category, namely 41.67%. The conclusion was science learning board (panjar) media in practical differentiated learning to improve students’ solving abilities.